Genotoxicity evaluation of domestic sewage in a municipal wastewater treatment plant - Grisolia, Cesar Koppe (2005)
An evaluation of the genotoxicity of domestic sewage was carried out in a municipal wastewater treatment plant. The study was carried out using Allium cepa root tip cells through cytological parameters such as aberrant cells in anaphase-telophase and the mitotic index, and the fish species Oreochromis niloticus and Tilapia rendalli, through the index of micronuclei in peripheral erythrocytes. In the Allium test, each of the four stages of the wasterwater treatment routine was analyzed, i.e., crude sewage, primary effluent, secondary effluent, and tertiary effluent. O. niloticus and T. rendalli specimens were maintained in an aquarium continuously receiving the final effluent, in an open system, before being discharged into Lake Paranoá. For micronuclei analysis, blood samples were drawn after 7, 21, 60, 102 and 142 days, respectively, in controlled conditions. The numbers of aberrant cells found in the Allium test did not differ among the four stages tested, nor when compared with the control. At all stages, the most concentrated sample was more toxic than the respective diluted samples, as demonstrated by the decreased mitotic index. Different sampling of the same group of fish revealed no increase in the micronuclei frequency, regardless of the period of exposure. A correlation between long-term exposure and micronuclei induction was not found either.